2011
DOI: 10.1186/1475-2867-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Different metastasis promotive potency of small G-proteins RalA and RalB in in vivo hamster tumor model

Abstract: BackgroundPreviously we have shown that oncogenic Ha-Ras stimulated in vivo metastasis through RalGEF-Ral signaling. RalA and RalB are highly homologous small G proteins belonging to Ras superfamily. They can be activated by Ras-RalGEF signaling pathway and influence cellular growth and survival, motility, vesicular transport and tumor progression in humans and in animal models. Here we first time compared the influence of RalA and RalB on tumorigenic, invasive and metastatic properties of RSV transformed hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…In HEK-HTRasV12 cells, the silencing of RalB impaired Transwell invasion of approximatively 60%, the silencing of RalA had not effect, and the silencing of both RalB and RalA reached up to 90% invasion inhibition ( Figure 5C ) (see Figure 5—figure supplement 1A for depletion efficiencies), indicating that Ras-dependent RalB activation substantially contributes to the invasive phenotype of Ras-mutated cells, and that RalA is dispensable, but it might partially compensate when RalB is absent. The specific role of RalB, with respect to RalA, for cell motility and invasion is in perfect agreement with several previous works ( Oxford et al, 2005 ; RossĂ© et al, 2006 ; Lim et al, 2006 ; Rybko et al, 2011 ). The RalB requirement for in vitro invasion of HEK-HTRasV12 cells was confirmed using the Inverted Invasion assay with collagen ( Figure 5D ) (see Figure 5—figure supplement 1B for depletion efficiency up to 5 days post-siRNA transfection).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In HEK-HTRasV12 cells, the silencing of RalB impaired Transwell invasion of approximatively 60%, the silencing of RalA had not effect, and the silencing of both RalB and RalA reached up to 90% invasion inhibition ( Figure 5C ) (see Figure 5—figure supplement 1A for depletion efficiencies), indicating that Ras-dependent RalB activation substantially contributes to the invasive phenotype of Ras-mutated cells, and that RalA is dispensable, but it might partially compensate when RalB is absent. The specific role of RalB, with respect to RalA, for cell motility and invasion is in perfect agreement with several previous works ( Oxford et al, 2005 ; RossĂ© et al, 2006 ; Lim et al, 2006 ; Rybko et al, 2011 ). The RalB requirement for in vitro invasion of HEK-HTRasV12 cells was confirmed using the Inverted Invasion assay with collagen ( Figure 5D ) (see Figure 5—figure supplement 1B for depletion efficiency up to 5 days post-siRNA transfection).…”
Section: Resultssupporting
confidence: 92%
“…RalB, but not RalA, is required for the contractility-driven invasion of lung cancer cells (A549, K-Ras mutated) ( Biondini et al, 2015 ). Moreover, in vivo metastasis assays in mice (tail vein injection) ( Ward et al, 2001 ; Lim et al, 2006 ) and in hamsters (subcutaneous injection) ( Rybko et al, 2011 ) supported a function of RalB pathway in the formation of tumor metastasis, both in Ras-mutated and Rous sarcoma virus-transformed cells. Besides the cancer context, we previously found that RalB, but not RalA, controls the mesenchymal migration of normal cells (NRK, HEK-HT, wild-type for Ras) by mobilizing its effector exocyst ( RossĂ© et al, 2006 ; Parrini et al, 2011 ; Biondini et al, 2016 ), which is an octameric protein complex involved in the tethering of secretory vesicles to the plasma membrane prior to SNARE-mediated fusion ( Wu and Guo, 2015 ).…”
Section: Introductionmentioning
confidence: 90%
“…Diminishing GTPase activity by RALA knock-down in HT-29 cells had no significant effect on proliferation supporting the notion that proliferation is mainly triggered by RAF/MAPK signaling. The migratory potential of these colorectal cancer cell lines was not affected by knocking-down RALA expression in contrast to other types of cancer cells [ 31 ]. This suggests that the migratory potential requires mechanisms controlled by other effector pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Pointed features make this model especially attractive for studying influence of different proteins on SMA. We have shown previously metastasis stimulating activity of some other G‐proteins, such as Ha‐Ras, RalA [Tchevkina et al, 2005], and RalB (Rybko et al, 2011, in press) using this cell line. However, we did not reveal significant effect of Arf6 on metastatic activity of HET‐SR cells.…”
Section: Discussionmentioning
confidence: 99%